Empowerment of Farmers Through GAPOKTAN to Improve Farmers' Welfare - Setiawan, Eko; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
The general background the empowerment of farmers is crucial for improving their welfare and ensuring sustainable agricultural development. Specific background This study focuses on the role of Farmer Group Associations (GAPOKTAN) in Dukuhsari Village as a platform for farmer empowerment. Knowledge gap Despite the recognized importance of farmer groups in community development, there is limited understanding of how these associations function to enhance farmers' welfare in specific contexts. Aims the research aims to analyze and describe the effectiveness of GAPOKTAN in empowering farmers within Dukuhsari Village. Results the findings indicate that GAPOKTAN has successfully facilitated the fulfillment of farmers' basic needs, improved access to resources, and fostered critical awareness among farmers. Participation of farmers in group activities has been instrumental in enhancing their involvement in agricultural management and empowerment processes. Novelty this study contributes to the existing literature by providing empirical evidence on the operational mechanisms of GAPOKTAN in a local context, highlighting its multifaceted role in promoting welfare among farmers. Implications the results suggest that strengthening GAPOKTAN and similar associations can lead to more effective agricultural policies and community development initiatives, ultimately contributing to better living standards for farmers and sustainable agricultural practices. Highlights: GAPOKTAN plays a crucial role in fulfilling farmers' basic needs. Participation in farmer groups enhances farmers' involvement in agricultural management. Critical awareness among farmers leads to better access to resources and support. Keywords: Farmer Empowerment, GAPOKTAN, Welfare, Participation, Community Development